Reasons for Polygamy and Its Impact on Muslim Family Life: Experiences of Polygamous Perpetrators in Babat, Lamongan, Indonesia - Hakim, Abdul (Journal of Islamic Law, 2022)
The discourse on polygamy has sparked controversy after Salafi clerics have intensively campaigned and practised polygamy. Meanwhile, the issue of polygamy is opposed by feminist activists because it is considered haram. For this reason, this article describes the contested responses of scholars regarding polygamy and its impact on Muslim family life in Babat, Lamongan, East Java, Indonesia. Using empirical research and a case study approach, the authors find that the concept of polygamy most compatible with Islamic family law in Indonesia is the concept of polygamy proposed by most fiqh scholars. They argue that polygamy is allowed under strict conditions, especially justice. The opinions of these scholars became the basis for the perpetrators to practice polygamy because his first wife was barren, requests from his first wife and interest in other women. The author finds that most polygamists impact disharmony in fostering family life, evidenced by the first wife and second wife always fighting. In addition, the author also finds a harmonious polygamous family. The husband's role as the head of the family who is firm and supported by wives who accept each other is the key to harmony in the family life of polygamists.